MANAJEMEN RISIKO TERHADAP BLACK SWAN EVENT MARET 2020 DI INDONESIA. STUDI KASUS EFEK COVID-19 TERHADAP PASAR MODAL INDONESIA - Andreas Kiky (Jurnal Bina Manajemen, 2020)
COVID-19 has caused many significant impacts on various businesses in Indonesia. This pandemic was first announced by government on March 2020 and as the result, Indonesia Composite Index moved toward down trend. To investigate this matter, this result applied event study and non-parametric test (Wilcoxon Signed Test) on observed IHSG from December 2019 to March 2020. The result confirmed that indeed after announcement, IHSG significantly decreased and loss almost 50% from initial value in December 2019. This research also suggests that this event cannot consider as Black Swan event because IHSG moved gradually decrease since February 2020. This research also offers some contingency plan and risk management concept to overcome this pandemic crisis.